Clinical efficacy and safety of Cadonilimab in the treatment of advanced gynecological malignancies: a retrospective, real-world study - Yisidan Huang; Yuting Zeng; Cui Zhang; Can Yang; Hanqun Zhang; Libo Li; Xiaoqing Luo; Yunchong Liu; Jiaying Bai; Fenghu Li; Yong Li (BMC Cancer)
Abstract Background Cadonilimab, recognized as the most rapidly developed Chinese drug in the field of cervical cancer, received marketing approval in China in 2022. We conducted a study to investigate the safety and efficacy of Cadonilimab, combined with and without chemotherapy or bevacizumab treatment, in patients with recurrent / metastatic gynecological malignancies. Methods We retrospectively enrolled 60 patients with recurrent / metastatic gynecological malignant tumors, confirmed by pathology or cytology from July 2022 to December 2024. All patients received at least two cycles of Cadonilimab. The primary endpoints were the investigator-confirmed objective response rate and disease control rate according to RECIST v1.1. Secondary endpoints included progression-free survival and safety. Results Fifty-six patients were included in the efficacy analysis. In the study population, This study is a retrospective real-world study, although it lacks a control group. There were 16 first-line patients with advanced cervical cancer, ORR was 81.3%(13/16,95% CI,57 to 93.4),DCR was 93.8%(15/16,95% CI 71.7 to 98.9); There were 30 second-line patients, ORR was 36.7%(11/30,95% CI,21.9 to 54.5),DCR was 90%(27/30,95% CI 74.4 to 96.5)。A total of 41 patients (73.2%) reported at least one treatment-related adverse event, with the most common being anemia (71.4%), nausea (28.6%), and myelosuppression (25%). 9 patients (16.1%) experienced G3-4 TRAEs. Additionally, 11 patients (19.6%) developed immune-related adverse events of G1-2. Importantly, no treatment-related deaths occurred during the study. Conclusion Cadonilimab with or without chemotherapy/bevacizumab had a promising antitumor activity and manageable safety profile in the treatment of recurrent/metastatic gynecological malignancies.